Cytotoxicity, proliferation and migration effects of 2,6-bis-(4-hydroxyl-3-methoxybenzylidine)cyclohexanone (BHMC) on human liver cancer, HepG2 cells - Mohd Shafiee, Muhammad Aminuddin; Syed Alwi, Sharifah Sakinah; Hanapi, Nur Aqilah Inani; Salaebing, Marwah; Othman, Zulkefley; Nurdin, Armania (Universiti Putra Malaysia Press, 2024)
Introduction: Natural bioactive substances have become increasingly noticeable for their capability to eliminate and counteract cancer throughout time. Curcumin, a bioactive compound derived from the rhizomes of turmeric, is well known for its therapeutic effect in inducing anti-inflammatory, anti-migration, and anti-proliferation activities. However, curcumin encounters several limitations that prevent it from reaching its maximum capabilities. One of the curcuminoid analogues, 2,6-bis-(4-hydroxyl-3-methoxybenzylidine)cyclohexanone (BHMC), was synthesized by removing the unstable β-diketone moiety and changing into double bonds while retaining the hydroxyl group to improve the curcumin’s bioavailability. It is aims to investigate the cytotoxicity of BHMC especially on the proliferation and migration effects towards human liver cancer, HepG2 cells. Methods: MTT assay was performed to determine the cytotoxicity of BHMC and curcumin on HepG2 and Hs27 cells. Next, Hoechst 33342 and Propidium Iodide staining were executed to observe the morphological changes on HepG2 cells treated with BHMC and curcumin. Further analysis on the migration rate of HepG2 cells upon treatment with BHMC and curcumin was measured using scratch assay. Results: At lower concentration, BHMC demonstrated approximately 3-7 times higher toxicity effect towards HepG2 cells compared to curcumin. BHMC also specifically targets HepG2 cells with a selectivity index of up to 6 units which clearly demonstrate its cytotoxic selectivity towards Hs27 cells. Further examination reveals that BHMC induces cytotoxicity via late-stage apoptosis. BHMC also enhanced the inhibition of the migration effects by 4.2, 7.2, and 7.6% throughout incubation period compared to the untreated and curcumin. Conclusion: Despite the pronounced toxicity of BHMC on HepG2 cells, BHMC was demonstrated more selective cytotoxic on Hs27.